Economic Analysis of International Interaction: International Economics and International Political Economy - A. G. Оleinov (Vestnik MGIMO-Universiteta, 2013)
The article focuses on two major fields of economic analysis of international interaction: international economics and international political economy. Each of the areas is considered through its formal methodological foundations. An attempt to formulate a general theoretical and methodological foundations of economic analysis of international interaction is made.